Methods of formation and development of biological concept at pupils (Journal of Educational Sciences, 2018)
Difference of school courses in biologу and life sciences determined bу the purpose, volume,structure, methods and forms of content. The purpose of science - to open the unknown side ofnature through research. The task of school courses – to explain the students the laws of sciencethrough the facts. To do this, it is verу important to form the minds of students in biological concepts.As part of the training program must be able to give them an explanation of the complex scientifictheories and problems. The important question is “how to teach?”, and “what to teach the students”.The course of biology unites in the methodology of genetic, morphological, anatomical, physiological,ecological, systematic, phylogenetic, cytological, embryological and agronomical sanitaryand medical approaches. The concept of the unity of life is the exchange of the transformation ofmaterial and energy, photosynthesis and chemosynthesis, autotrophic and heterotrophic organisms,etc. All this leads to an understanding of the new ecological epoch - the noosphere, reflecting thehistorical development of the biosphere, human labor and thinking as the crust of the earth’s crust. Botany, zoology, human anatomy, physiology and health, as well as general courses of biology,reveal not only the laws of development of individual organisms, but also the laws of the historicaldevelopment of organisms.When studying the types of plants and animals, pupils should acquireelementary concepts about the development of the organic world. The paper summarizes the experienceof studying the lessons of Biology, conducted an experimental- pedagogical investigation. Themethodology of teaching Biology is presented with an emphasis on the clarification of biologicalscientific concepts. Pupils of the 9th grade of school No. 139 of Almaty took part in an experimentalpedagogical investigation.Keу words: integration, deductive, transductive, inductive, abstract, didactics.